2004
DOI: 10.1038/ng1330
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inactivation of SFRP genes allows constitutive WNT signaling in colorectal cancer

Abstract: Aberrant WNT pathway signaling is an early progression event in 90% of colorectal cancers 1 . It occurs through mutations mainly of APC and less often of CTNNB1 (encoding β-catenin) 1-3 or AXIN2 (encoding axin-2, also known as conductin) 4 . These mutations allow ligandindependent WNT signaling that culminates in abnormal accumulation of free β-catenin in the nucleus 1-3 . We previously identified frequent promoter hypermethylation and gene silencing of the genes encoding secreted frizzledrelated proteins (SFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
863
4
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 962 publications
(929 citation statements)
references
References 28 publications
59
863
4
3
Order By: Relevance
“…As negative controls, we prepared cells expressing either the homologous C18 polypeptide lacking the frizzled module (V2Nter-HCT116) or empty pCDNA3.1 vector (Vector-HCT116, Figures 1a and b). In HCT116 cells, transient expression of V3Nter, SFRP-1 or SFRP-5 induces cell death (Suzuki et al, 2004;Quelard et al, 2008). Consistently, attempts to obtain clones by limiting dilution were unsuccessful, suggesting a negative selection pressure, as shown for SFRP-1 in breast cancer cells (Bafico et al, 2004).…”
Section: Hct116 Colorectal Cancer Cells Stably Expressing V3ntermentioning
confidence: 67%
See 4 more Smart Citations
“…As negative controls, we prepared cells expressing either the homologous C18 polypeptide lacking the frizzled module (V2Nter-HCT116) or empty pCDNA3.1 vector (Vector-HCT116, Figures 1a and b). In HCT116 cells, transient expression of V3Nter, SFRP-1 or SFRP-5 induces cell death (Suzuki et al, 2004;Quelard et al, 2008). Consistently, attempts to obtain clones by limiting dilution were unsuccessful, suggesting a negative selection pressure, as shown for SFRP-1 in breast cancer cells (Bafico et al, 2004).…”
Section: Hct116 Colorectal Cancer Cells Stably Expressing V3ntermentioning
confidence: 67%
“…It has been suggested that SFRPs may function as tumor suppressors in CRC because allelic loss or epigenetic inactivation of SFRP genes contributes to constitutive activation of the Wnt/b-catenin pathway (Caldwell et al, 2004;Suzuki et al, 2004). In this context, we and others have shown that restoring expression of SFRP-1 or SFRP-5 inhibits Wnt/b-catenin stabilization and induces in vitro cell death in human CRC cells (Suzuki et al, 2004;Quelard et al, 2008).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations